Abnormal Corneal Lesions Induced by Trastuzumab Emtansine: An Antibody–Drug Conjugate for Breast Cancer. Issue 10 (October 2016) - Tsuda, Mayuko; Takano, Yoji; Shigeyasu, Chika; Imoto, Shigeru; Yamada, Masakazu
Abstract : Purpose: To report a case of atypical corneal lesions presumably induced by trastuzumab emtansine, an antibody–drug conjugate that is designed to selectively deliver cytotoxic agents to human epidermal growth factor receptor 2 (HER2)–positive breast cancer cells. Case: A 64-year-old Japanese woman developed bilateral corneal epithelial abnormalities that originated from the limbus. The corneal lesions covered the superior area in the right eye and both superior and inferior areas including the visual axis in the left eye. The patient had advanced ductal carcinoma of the left breast and had been receiving anticancer treatment with trastuzumab emtansine for 15 months. After switching the chemotherapy from trastuzumab emtansine monotherapy to the combination of docetaxel, trastuzumab, and pertuzumab, the abnormal corneal lesions showed gradual improvement. Conclusions: As corneal epithelial cells express human epidermal growth factor receptor 2 under normal conditions, such cells may also be targeted by trastuzumab emtansine and lead to corneal epithelial lesions.